Milly, Molly and Heidi Untidy - Pittar, Gill; Morrell, Cris (MM House Pub. Gisborne, N.Z., 2003)
Milly and Molly's friend Heidi Untidy learns the value of tidiness when she loses her favourite book in her messy bedroom. Includes teaching guide. Suggested level: junior